Traumatic L5-S1 spondylolisthesis: A case report: Poškodbena spondilolisteza L5-S1: prikaz primera - Movrin, Igor (Acta Medico-Biotechnica, 2023)
Purpose: Here, we report the diagnosis and management of a patient with a traumatic lumbosacral spondylolisthesis, a rare clinical entity that is characterized by unilateral or bilateral facet dislocations causing displacement at the level of the fifth lumbar vertebra in relation to the sacrum. Case presentation: We report a case of a traumatic L5-S1 unilateral lumbosacral dislocation. Based on the preoperative CT and MRI findings, the patient sustained a right-side unilateral L5–S1 subluxation with an L5 right inferior articular process fracture, a torn anterior longitudinal ligament and posterior ligamentous complex, and L5-S1 disc protrusion. Decompression, reduction with L4, L5, S1 pedicular screw fixation, L5-S1 disc excision, and interbody cage insertion were performed. The patient had an uneventful recovery and returned to his previous activities 6 months after surgery.
Keywords: traumatic spondylolisthesis, pedicle screw fixation, ligamentous rupture, interbody cage, lumbar interbody fusion